Hypertonic Resistance of Human Fetal Erythrocytes in Electrolyte Medium - Kuleshova, L. G. (Problems of Cryobiology and Cryomedicine, 2003)
Using the method of spectrophotometry there was studied the kinetics of free hemoglobin accumulation in supernatants after exposure of human fetal erythrocytes in NaCl hypertonic solutions. There was demonstrated that an increased, if compared with the adult donor’s erythrocytes long-term resistance, (60 min) of fetal erythrocytes to hyperosmotic effect up to 2.3 M could be stipulated by the presence in fetal blood of a considerable amount of young forms of erythrocyte.